2017
DOI: 10.1371/journal.pgen.1006703
|View full text |Cite
|
Sign up to set email alerts
|

Triplin, a small molecule, reveals copper ion transport in ethylene signaling from ATX1 to RAN1

Abstract: Copper ions play an important role in ethylene receptor biogenesis and proper function. The copper transporter RESPONSIVE-TO-ANTAGONIST1 (RAN1) is essential for copper ion transport in Arabidopsis thaliana. However it is still unclear how copper ions are delivered to RAN1 and how copper ions affect ethylene receptors. There is not a specific copper chelator which could be used to explore these questions. Here, by chemical genetics, we identified a novel small molecule, triplin, which could cause a triple respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 51 publications
1
34
0
1
Order By: Relevance
“…S4A). It has been shown that AtATX1-mCherry is localized to the cytoplasm and nucleus and adheres to endoplasmic reticulum membranes (Puig et al, 2007;Li et al, 2017).…”
Section: Subcellular Localization Of Osatx1mentioning
confidence: 99%
See 4 more Smart Citations
“…S4A). It has been shown that AtATX1-mCherry is localized to the cytoplasm and nucleus and adheres to endoplasmic reticulum membranes (Puig et al, 2007;Li et al, 2017).…”
Section: Subcellular Localization Of Osatx1mentioning
confidence: 99%
“…In Arabidopsis, AtATX1 was proposed to deliver Cu to AtHMA5 for Cu detoxification in roots Huang et al, 2016). Using triplin as a Cu ion chelator, AtATX1 was shown to act upstream of RAN1 for Cu + delivery (Li et al, 2017). In rice, the expression of OsHMA4, OsHMA5, OsHMA6, and OsHMA9 was The wild-type yeast strain BY4741 and its mutant strain Δycf1 were transformed with the empty vector pYES2 or OsATX1.…”
Section: Osatx1 Affects Cu Transport and Distribution Probably By Intmentioning
confidence: 99%
See 3 more Smart Citations